Political messaging, parliament, and people, or, Why politicians say the things they do the way they do : the Parliamentary Green Party of Aotearoa New Zealand in 2013 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University, Palmerston North, Aotearoa New Zealand - Bignell, Jessica Anne Copplestone (Massey University, 2018)
One of the main things a Member of Parliament (MP) does in their everyday work is talk. They are constantly saying things to try to win over the public’s support and make the world they envision real. This thesis is about politicians’ statements: why they say the things they say the way they do. Based on behind-the-scenes ethnographic fieldwork in the parliamentary offices of the Green Party of Aotearoa New Zealand, I explore the difficult strategic work that shapes what opposition MPs say. In order to win over the public support they need to increase their vote, MPs have to communicate effectively in adherence to the rules and codes of political messaging, be good oppositional MPs, and speak and act in ways that fit authentically with their dispositions. I show that, unlike the simple soundbites we see in public from our politicians, the production of statements designed to win support is messy, indeterminate, uncertain, filled with tension and –above all – intensely complex. Drawing on Bourdieu’s theory of practice and analysis of the political field, I argue that managing that complexity to make political statements that aim at winning the political stakes and fit the specific situation, MPs must rely on their practical sense: their feel for the game that allows them to anticipate and shape the future state of play from the current situation. Because the language used to describe the world constitutes the social order that makes it real, this thesis examines how the three drivers of modern political communication, the structure of parliament, and the dispositions of individuals preconstrain what politicians can say and therefore the possibilities of the world MPs can aim at creating.
Keywords: Green Party of Aotearoa New Zealand; Communication in politics; New Zealand; Politics and government; 21st century; political communication; political strategy; messaging; Parliament; opposition; Member of Parliament; Bourdieu